A study on the employment and wage outcomes of people with disabilities - Sevane Ananian; Giulia Dellaferrera (International Labour Organization (ILO), 2024)
This study investigates the employment and wage disparities between people with and without disabilities. It shows that individuals with disabilities are less likely to participate in the labour market, and that when they do, they face higher unemployment rates, are more likely to be self-employed and tend to earn lower wages. These disparities do not appear to be explained solely by individual characteristics such as educational attainment, experience or occupational category. They are most likely driven by various other factors as well, including limited provision of work place accommodations in many firms, the potentially greater job flexibility offered by self-employment, and discrimination against people with disabilities. In its final section, the study high lights legal frameworks established at the international and national levels to promote equal opportunities and fair remuneration for people with disabilities.
Keywords: 330; Disabled workers; employment; unemployment; self-employed; wage structure; disability policy; Behinderte Arbeitskräfte; Erwerbstätigkeit; Arbeitslosigkeit; Selbstständige; Lohnstruktur; Behindertenpolitik; Welt